Quick Evaluation on Preterm Baby Developmental Care Model Focusing on the Suitable Component and Intervention in Indonesia - Syamsu, Andi Fatmawati; Sulisnadewi, Niluh Komang; Hadriani, Hadriani; Rizkaningsih, Rizkaningsih (Poltekkes Kemenkes Palu, 2023)
Introduction: The neonatal stage is important because of its high mortality risk. Neonatal Intensive Care Unit (NICU) is both an important and dangerous place for preterm babies since it can increase the developmental disorders in the baby. Various programs containing several early interventions for preterm babies are implemented and combined into a developmental care model. Objective: This study identified the components, contents, and interventions in the developmental care model for preterm babies that is suitable for Indonesia. Method: This qualitative research was done through Rapid Assessment Procedures (RAP) to produce information quickly to help decision-making, continued by content analysis using Microsoft Excel through several stages, namely case classification, condensing, streamlining meaning, and compiling, hence producing subcontent. Results: The DSC developmental care model looks more detailed, while NIDCM has core components of teamwork and collaboration that are not found in the DSC, thus complementing each other. Conclusion: The NIDCM developmental care model is more applicable than DSC since it can be done in the NICU with limited human resources or staff that are not yet fully trained. Both interventions need to be made shorter, and terms can be created as a combination of both so that they become alternative developmental care.